Lifestyle Behaviors and Risk of Metabolic Syndrome: A Case-Control Study among Fishermen and Oil Palm Farmers - Verawati, Besti; Riyadi, Hadi; Khomsan, Ali; Ekayanti, Ikeu (Journal of Health and Nutrition Research, 2025)
Metabolic syndrome (MetS) is a growing health concern in Indonesia, particularly in rural communities with limited healthcare access. Behavioral risk factors such as smoking, coffee consumption, and poor health-seeking behavior (HSB) may increase MetS risk in vulnerable populations. This study aimed to examine the association between lifestyle behaviors—smoking, coffee consumption, and HSB—and the risk of MetS among fishermen and oil palm farmers in Aceh, Indonesia.  A case-control study was conducted among 240 adults, comprising 120 couples,  recruited from rural fishing and farming communities. Cases met the IDF 2020 MetS criteria, while controls did not. Data on sociodemographics, smoking, coffee intake, and HSB were collected via structured interviews and clinical assessments. Multivariate logistic regression was used to identify independent risk factors, adjusting for age, gender, and education. Smoking among husbands (AOR = 2.89; 95% CI: 1.19–7.02; p = 0.019), coffee consumption (AOR = 2.40; 95% CI: 1.00–5.79; p = 0.049), and low HSB (AOR = 3.10; 95% CI: 1.35–7.11; p = 0.008) were significantly associated with higher odds of MetS. While age and education were not independently significant, they were retained in the model as potential confounders. This study highlights the need for tailored health promotion targeting smoking cessation, improved health service engagement, and dietary awareness in rural Indonesian populations. Interventions should consider sociocultural practices such as sweetened coffee consumption to reduce MetS risk effectively.